Propagation of Phellinus linteus originated from An Giang, Vietnam - Ba, H. T. T.; An, P. T.; Luong, V. V. (International Journal of Agricultural Technology, 2024)
A wild mushroom species from the highland regions of An Giang province, Vietnam, was identified as Phellinus linteus AG (commonly known as Sang-Hwang mushroom) through a combination of morphological characteristics and ITS sequence comparison. The ITS sequences, amplified using the primer pair ITS1 (5'-TCCGTAGGTGAACCTGCGG-3') and ITS4 (5'-TCCTCCGCTTATTGATATGC-3'), showed a 92% similarity to those in the GenBank database. The optimal medium for the first propagation phase was potato dextrose agar (PDA), with complete hyphal growth observed after 7 days. For the second propagation phase, paddy was found to be the best medium, also achieving full hyphal growth in 7 days. The most suitable medium for producing a high yield of fruiting bodies consisted of 90% rubber sawdust + 5% rice bran + 5% corn flour. Fruiting bodies developed after 33 days, and were ready for harvest after 55 days, with a biological efficiency of approximately 0.47%.